การพัฒนาทักษะการเป็นผู้ประกอบการในเด็กปฐมวัย - ภูคงสด, อารีพร; ชนะโยธา, พรทิวา; ประชาโรจน์, อภัสรา (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด, 2024)
ทักษะพื้นฐานที่สำคัญของการเป็นผู้ประกอบการคือ การมีความคิดสร้างสรรค์และความคิดยืดหยุ่น เพื่อการสร้างสิ่งใหม่ๆที่ต่างไปจากเดิม มีเป้าหมาย มีความเพียร การยอมรับความสำเร็จ ความผิดหวัง และมีความสามารถในการแก้ไขปัญหาการปลูกฝังทักษะพื้นฐานที่สำคัญของการเป็นผู้ประกอบการให้กับเด็กจึงเป็นสิ่งที่ดี โดยเฉพาะเด็กปฐมวัยที่เป็นวัยที่สมองเจริญเติบโต การส่งเสริมทักษะการเป็นผู้ประกอบการ ไม่ใช่แค่การที่เด็กเติบโตและสามารถสร้างธุรกิจของตัวเองได้ แต่ยังรวมไปถึงการเป็นผู้ที่สามารถมีทางเลือกในอาชีพ รู้เท่าทันโลกที่ไม่แน่นอน และพร้อมรับการเปลี่ยนแปลงในปัจจุบันและอนาคต การพัฒนาการเป็นผู้ประกอบการให้กับเด็กปฐมวัย สามารถในรูปแบบกิจกรรมได้หลากหลาย เช่น การเรียนการสอนแบบโครงการ (project approach)เป็นการศึกษาหาความรู้ อย่างลุ่มลึก เด็กได้พัฒนาการสื่อสาร แสดงความสามารถ ค้นหาทางแก้ปัญหา เสนอกระบวนการแก้ปัญหาที่คิดค้นขึ้น กิจกรรมทัศนศึกษาเด็กเรียนรู้ผ่านการลงมือปฏิบัติ เด็กจะจดจำจากประสบการณ์ รวมทั้งพัฒนาความคิดรวบยอดในเชิงบวกผ่านกิจกรรม กิจกรรมทำอาหาร (Cooking) เป็นกิจกรรมเพิ่มพูนประสบการณ์การเรียนรู้ส่งเสริมทักษะการเป็นผู้ประกอบการในเด็กปฐมวัยอย่างเป็นองค์รวม  กิจกรรมตลาดนัดอาชีพเป็นกิจกรรมที่จัดขึ้นมีจุดมุ่งหมายจำลองสถานการณ์เสมือนตลาดจริง เด็กจะทำหน้าที่เป็นผู้ขายและผู้ซื้อ จากการใช้เหรียญและธนบัตรของจริง กิจกรรมที่เด็กได้ลงมือกระทำด้วยตนเองทั้งทางตรงและทางอ้อมเด็กเกิดทักษะการเป็นผู้ประกอบการ และสามารถนำไปใช้ให้เกิดประโยชน์ในชีวิตประจำได้ต่อไป Basic skills in entrepreneurship are creativity and flexibility so as to make new things a different way with goals, perseverance, acceptance for success, disappointment, and problem-solving ability. Instilling basic skills in entrepreneurship in children is a good thing, especially in early childhood children, the age of the brain growth. Promoting entrepreneurship skills is not only the way children grow up and are able to create their own business but also the ability to make their own career choice, have literacy in the changing world, and getting ready to accept current and future changes.  The development of entrepreneurship skills for early childhood can be implemented through various activities, such as the project approach to teaching and learning. It is a set of teaching strategies that enable teachers to guide students through in-depth studies. Children have a chance to develop their communication skills, express their abilities, find a way to solve a problem, present a process of how a problem is solved, field trip activities; children learn from practices. They remember from experiences they obtain including developing a positive concept through activities, cooking activity; an activity that enhances learning experiences and promotes holistic entrepreneurship skills, professional flea market activity; it is an activity established to simulate the real atmosphere of a market. Children are allowed to be buyers and sellers and learn how to use coins and bank notes. Activities that encourage children to practice by themselves, both directly and indirectly, shall generate entrepreneurship skills which can be used in their real life in the future.